Age-related decline of neuroplasticity to intermittent theta burst stimulation of the lateral prefrontal cortex and its relationship with late-life memory performance. Issue 9 (September 2020) - Goldsworthy, Mitchell R.; Rogasch, Nigel C.; Ballinger, Sophie; Graetz, Lynton; Van Dam, Jago M.; Harris, Richard; Yu, Solomon; Pitcher, Julia B.; Baune, Bernhard T.; Ridding, Michael C.
Highlights: Combined TMS-EEG was used to assess neuroplasticity in the ageing prefrontal cortex. Neuroplastic response to iTBS was reduced in older relative to young adults. Reduced neuroplasticity was associated with poorer memory performance in older adults. Abstract: Objective: Advanced age is accompanied by a deterioration in memory performance that can profoundly influence activities of daily living. However, the neural processes responsible for age-related memory decline are not fully understood. Here, we used transcranial magnetic stimulation (TMS) in combination with electroencephalography (EEG) to assess age-related changes in neuroplasticity in the human prefrontal cortex. Methods: TMS-evoked cortical potentials (TEPs) were recorded before and following the neuroplasticity-inducing intermittent theta burst stimulation (iTBS), applied to the left lateral prefrontal cortex in healthy young (n = 33, mean age 22 ± 3 years) and older adults (n = 33, mean age 68 ± 7 years). Results: iTBS increased the amplitude of the positive TEP component at 60 ms after the TMS pulse (P60) in young, but not older adults. This age-related decline in P60 plasticity response was associated with poorer visuospatial associative (but not working) memory performance in older adults. Conclusions: These findings suggest that neuroplasticity in the human lateral prefrontal cortex is reduced in older relative to young adults, and this may be an important factor in age-related memory decline. Significance: This may have important implications for the early detection of cognitive decline and dementia.